Coagulase gene polymorphism of Staphylococcus aureus isolates: A study on dairy food products and other foods in Tehran, Iran - Mohammad Mehdi Soltan Dallal; Mohammad Reza Khoramizadeh; Solmaz Agha Amiri; Ali Akbar Saboor Yaraghi; Ramin Mazaheri Nezhad Fard (Food Science and Human Wellness)
Coagulase is considered as a major determinant factor for the identification of Staphylococcus aureus strains. The 3′-end coding region of the coagulase (coa) gene contains a series of 81-bp tandem repeats, which differ in the number and location of enzymatic restriction sites among different isolates. coa PCR-RFLP has been used widely to type S. aureus isolates in epidemiological studies. The current study was conducted to investigate the coagulase gene polymorphisms in S. aureus isolated from various food samples using an in house PCR-RFLP method. A total of 100 strains of S. aureus were isolated from food samples. Isolates were typed by PCR-RFLP analysis using NdeI restriction digestion of the coagulase gene PCR products. Results showed that amplification of coagulase genes from S. aureus produced different PCR products. The isolates were grouped into 18 genotypes using RFLP analysis results of the genes. In this study, the S. aureus isolates have been shown to include more than one coagulase genotype, but only had a few coa genotypes predominated.